Key concepts in public archaeology - Moshenska, Gabriel (Open Access e-Books., 2017)
This textbook provides a broad overview of the key concepts in public archaeology, a research field that examines the relationship between archaeology and the public, in both theoretical and practical terms. Written for students and practitioners, the individual chapters - which can be read independently - provide textbook-level introductions to the themes, theories and controversies that connect archaeology to wider society, and point readers to relevant case studies and learning resources to aid further study.